Diversity in sound pressure levels and estimated active space of resident killer whale vocalizations - Miller, Patrick (Journal of Comparative Physiology A, 2006)
Signal source intensity and detection range, which integrates source intensity with propagation loss, background noise and receiver hearing abilities, are important characteristics of communication signals. Apparent source levels were calculated for 819 pulsed calls and 24 whistles produced by free-ranging resident killer whales by triangulating the angles-of-arrival of sounds on two beamforming arrays towed in series. Levels in the 1-20 kHz band ranged from 131 to 168 dB re 1 mu Pa at 1 m, with differences in the means of different sound classes (whistles: 140.2 +/- 4.1 dB; variable calls: 146.6 +/- 6.6 dB; stereotyped calls: 152.6 +/- 5.9 dB), and among stereotyped call types. Repertoire diversity carried through to estimates of active space, with "long-range" stereotyped calls all containing overlapping, independently-modulated high-frequency components (mean estimated active space of 10-16 km in sea state zero) and "short-range" sounds (5-9 km) included all stereotyped calls without a high-frequency component, whistles, and variable calls. Short-range sounds are reported to be more common during social and resting behaviors, while long-range stereotyped calls predominate in dispersed travel and foraging behaviors. These results suggest that variability in Sound pressure levels may reflect diverse social and ecological functions of the acoustic repertoire of killer whales.